CATASTROPHIC ANTIPHOSPHOLIPID SYNDROME – CASE REPORT - Hashim, Tarig; Omer, Ahmed; Abdelateef, Gubara (Gezira Journal of Health Sciences, 2011)
A 26 year old lady, her first pregnancy complicated by abruptio placentae at term without obvious cause, outcome was fresh stillbirth. In her second pregnancy, she developed severe headache at seven weeks gestation, confusion, apathy, dementia, fits and left lower limb swelling within a period less than 10 days. Magnetic resonance imaging (MRI) revealed bilateral sinus thrombosis. Low molecular weight heparin (Innohep) was started immediately and gradually increased adjusted by (PTT). The patient gradually improved and discharged on Innohep. In spite of, injectable anticoagulant therapy, she developed intrauterine fetal death at seven month. She delivered spontaneously. The first result of screening for antiphospholipid antibodies was positive with low protein S. She was diagnosed as probable catastorophic antiphospholipid syndrome (APS). She was discharged on oral anticoagulant (warfarin) with adjusted dose according to PT & INR. After a year of warfarin therapy, with laboratory follow-up, the second result of screening antiphospholipid antibodies remained positive with lower protein S., compared with the first result and; drop in protein C, which increases the incidence of thrombosis and makes further pregnancy unadvisable.